Evaluation of the Sensory Correlation between Touch Sensitivity and the Capacity to Discriminate Viscosity. Issue 2 (27th March 2015) - Aktar, Tugba; Chen, Jianshe; Ettelaie, Rammile; Holmes, Melvin
Abstract The capacity to discriminate the viscous nature of food materials is critically important in the sensory evaluation and subsequent perception of food texture and acceptability. It is generally assumed that this capability is closely linked to individual's tactile sensitivity, which in itself is a function of the individual's specific capabilities due to experience, age, lifestyle and health status for example. However, no experimental evidence is yet available to validate or disprove this assumption. By comparing the touch sensitivity and the capability of viscosity discrimination among individuals (using finger and tongue sensory perception), this work aims to establish if a correlation exists. Semmes‐Weinstein monofilaments were used for touch sensitivity tests of the index fingers and tongue surfaces. A series of syrup solutions were prepared to give a wide range of viscosities with a viscosity scale factor of 1.2 ± 0.009. A total of 30 healthy subjects (16 female and 14 male; mean age 29.9 ± 9 years; mean body mass index 22.5 ± 2.9 kg/m2) participated in this study. A similar touch sensitivity threshold, 0.023 and 0.021 g, was observed for the index fingertip and for the tongue, respectively. However, the tongue appears to be more sensitive to touch than the fingertips when the force range they cover was compared. The viscosity discrimination threshold was found to be approximately 53% for the index fingertip and around 47% for the tongue. By comparing individual capabilities of viscosity discrimination against touch sensitivity, no significant correlation was observed between the two factors. The results from this work suggest that the capability to discriminate viscosity differences is more likely attributed to experience and is little influenced by one's physiological capability of tactile sensation, e.g., the touch sensitivity. Practical Applications The capability to discriminate differences in viscosity and the subsequent perception is an important factor for food texture appreciation. Establishment of the underlying factors that characterize the variation in the ability for such discrimination across individuals is not only critically important for our fundamental understanding of the viscosity perception but is also hugely important for the food industry in development of new food products, and in particular for specific food design for individuals with special needs, e.g., elderly, dysphagia patients, etc. Differential threshold for certain tastes and aroma compounds has been investigated. However, little has been reported in the literature about the tactile interpretation of viscosity sensation and perception. Findings from this work could provide new insight for researchers in the food industry and in food development by giving them flexibility to redesign their ingredients especially the one that has thickening effect on the product viscosity. Methodologies used in this experiment could also be applied for general food sensory studies in establishing relationships between sensory psychology and sensory physiology and especially the threshold studies with a similar approach of finding just noticeable difference values of any stimuli. The method could also be applicable to sensory capability studies of some particular groups such as elderly people to assess how weakened physiology affects their sensory capability.